2011
DOI: 10.1680/geot.8.t.015
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation around partially embedded seabed pipelines

Abstract: When a pipeline is laid on a soft clay seabed, excess pore pressure is generated. During the subsequent dissipation process, the effective stress at the pipe-soil interface and the available axial pipe-soil resistance rise. This 'set-up' of axial resistance is an important consideration in various aspects of pipeline design, including the mitigation of thermal and pressure-induced expansion, the stability of the pipeline on sloping ground and the assessment of pipe-soil forces during installation. A set of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…This contrast in the fsu parameter between surface foundations and pipelines is perhaps due to the additional normal stress applied to the surrounding soil by the 'wedging' effect (Krost et al, 2011) caused by the curved pipeline surface. This additional loading creates a greater rise in soil strength than the purely vertical load applied by a surface foundation.…”
Section: Simplified General Relationships For Consolidated Breakout Rmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast in the fsu parameter between surface foundations and pipelines is perhaps due to the additional normal stress applied to the surrounding soil by the 'wedging' effect (Krost et al, 2011) caused by the curved pipeline surface. This additional loading creates a greater rise in soil strength than the purely vertical load applied by a surface foundation.…”
Section: Simplified General Relationships For Consolidated Breakout Rmentioning
confidence: 99%
“…Gourvenec and White (2010) and Krost et al (2011) presented elastic solutions of the consolidation response which indicated the extent and longevity of the excess pore pressures around a pipeline but the elastic soil model used in the analyses precluded assessment of the subsequent resistance. Chatterjee et al (2012b) performed elasto-plastic finite element analysis using the modified Cam clay constitutive model to study consolidation rates around pipelines and these analyses were extended by Chatterjee et al (2013) to examine the changes in bearing capacity for consolidation under a load equal to the initial undrained bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts in the literature to model coupled consolidation behaviour under partially embedded pipes have mainly been limited to small-strain elastic solutions (Gourvenec and White 2010;Krost et al 2011). The prediction of pore-water pressure dissipation assuming the soil to be elastic can be reasonably accurate.…”
Section: Introductionmentioning
confidence: 99%
“…However, a poroelastic model, with the assumption of linear elasticity, is the common starting point for many (if not most) closed form solutions for consolidation problems. They have been shown to give good approximations for the consolidation behaviour (see for example Randolph andWroth, 1979 andKrost et al, 2010).…”
Section: Introductionmentioning
confidence: 99%